Corporate governance in China - Chen, Jian, 1962 February 6- (RoutledgeCurzon studies on the Chinese economy, 2005)
This book examines key questions relating to corporate governance in China, including the relationship between ownership structure and corporate performance, the determinants of capital structure, and the nature of contemporary governance structures.